Women Health, Maternal Health and HIV infection in West Africa - (:unkn) unknown (My University, 2014)
HIV infection in sub-Saharan Africa is a major public health threat particularly for girls and women ofreproductive age. The research presented in this thesis was conducted particularly in West Africa andthe specific objectives are i) to estimate the prevalence of intimate partner violence according to HIVserological status; ii) to estimate the incidence rate of pregnancy following ART initiation; iii) todetermine the effect of pregnancy after ART initiation on the risk of death, HIV-disease progressionand loss to follow-up. Firstly, in Togo, According to our findings, the prevalence rates of lifetimephysical and sexual violence (IPV) among HIV-infected women were significantly higher thanamong uninfected women (63.1 vs. 39.3%, p=0.01 and 69.7 vs. 35.3%, p=0.01, respectively).Secondly, Among HIV-infected West African women, the crude incidence of first pregnancy afterART initiation was 2.9 per 100 women-years [95% confidence interval (CI): 2.7 to 3.0] and it could beas high as 4.7 per 100 women-years (95% CI: 4.3 to 5.1) among women aged 25-29 years old. Finally,pregnancy after ART initiation appeared to reduce the risk of death or HIV-disease progression(Adjusted Hazard Ratio [aHR] =0.61; 95%CI: 0.40-0.92) and the risk of becoming LTFU at M48(aHR=0.74; 95%CI: 0.60-0.92) among West African HIV-infected women. Intimate partner violence ishighly prevalent among HIV-infected women and it may have negative repercussions on their healthstatus. Pregnancy is a common event after ART initiation and it might have repercussions on thehealth status of HIV-infected women. The design of safe motherhood programs addressed to HIVinfectedwomen and its integration within HIV care services must are a public health priority in sub-Saharan Africa.
Keywords: African Research